EKONOMI INDUSTRI PULP DAN KERTAS INDONESIA: ANALISIS SIMULASI KEBIJAKAN DAN TEKANAN INTERNASIONAL - Bambang Widyantoro; Hermanto Siregar; Bunasor Sanim; D.S. Priyarsono (School of Business, Bogor Agricultural University (SB-IPB), 2006)
The objectives of this study are to evaluate the impacts of relevant policy alternatives and international pressure for Indonesian pulp and paper industries on the domestic economy. Ten policy alternatives set for period 1993-2003 are simulated with a simultaneous econometric model. The two-stage least squares method was used to estimate the parameters of the behavioral equations in the model. Using income distribution and welfare criterias, the results indicate that the objective of decreasing pulp price will improve the welfare of Indonesian society. It is essential that the policies would avoid a monopsony of pulpmills for the timber-estate and a monopoly for the papermills. Not significantly, the distribution of replanting fund will improve in a little of the domestic economy. Since the distribution of the fund be stopped, then producers' surplus will decline and the highest income distribution will be received by small-log producers, and the income transfer effects result a net welfare gain to Indonesian society. Stock dictation will be the domestic economy worse-off, but that would not be a case in the export embargo. Indonesia will loss in foreign exchange receipts because of the decreasing interest rate and international pressures. The domestic economy will decline due to this policies and pressure, so the net transfer effects are a welfare loss to Indonesian society as a whole